2006
DOI: 10.1115/1.2753887
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Turbulent Heat Transfer and Pressure Drop Characteristics in a Water-Cooled Minichannel Heat Sink

Abstract: With the rapid development of the Information Technology (IT) industry, the heat flux in integrated circuit (IC) chips cooled by air has almost reached its limit at about 100W∕cm2. Some applications in high technology industries require heat fluxes well beyond such a limitation. Therefore, the search for a more efficient cooling technology becomes one of the bottleneck problems of the further development of the IT industry. The microchannel flow geometry offers a large surface area of heat transfer and a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Kandlikar and Upadhye [12] appreciably extended the heat flux limit by using the microchannel designs and had proposed an optimization procedure for selecting the geometries of the microchannel under the given pressure condition. Also, Xie et al [13,14] provided a series of numerical studies on the heat transfer and pressure drop characteristics in microchannel heat sinks for chip cooling and concluded that utilization of a thinner thickness of bottom and channel could improve heat transfer performance for both laminar and turbulent flows with acceptable pressure drop penalty.…”
Section: Introductionmentioning
confidence: 98%
“…Kandlikar and Upadhye [12] appreciably extended the heat flux limit by using the microchannel designs and had proposed an optimization procedure for selecting the geometries of the microchannel under the given pressure condition. Also, Xie et al [13,14] provided a series of numerical studies on the heat transfer and pressure drop characteristics in microchannel heat sinks for chip cooling and concluded that utilization of a thinner thickness of bottom and channel could improve heat transfer performance for both laminar and turbulent flows with acceptable pressure drop penalty.…”
Section: Introductionmentioning
confidence: 98%
“…Based on the results, the conventional Navier-Stokes equations could be used to predict flow and heat transfer in the microchannels. Xie et al [13,14] investigate numerical studies on the laminar and turbulent flow and heat transfer characteristics of water-cooled straight microchannel heat sink. It showed that the removed heat flux increased from 256 W/cm 2 to 350 W/cm 2 with a nearly-optimized microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…The governing equations are continuity, momentum, and energy equations together with the standard k-e model, which are well documented in literature [4] and omitted here for simplicity.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Mini-channel heat sink has been considered as an effective heat removal tool and has caught much attention during the past decades, due to its advantages including high heat transfer performance, mild pressure loss and easy fabrication [4,5]. Much research has been conducted on the heat transfer and fluid flow characteristics of mini-channels, and most of them suppose that the inlet velocities of all the channels are the same [3][4][5][6][7]. Garimella and Sobhan [8] presented their results of theoretical and experimental studies in mini-channels under different flow regimes, and pointed out that fluid flow and heat transfer characteristics in mini-channels with the hydraulic diameter within 0.2-3 mm are still in accordance with conventional ones.…”
Section: Introductionmentioning
confidence: 99%